Geology of the Alpha Regio (V-32) Quadrangle, Venus. Issue 2 (3rd July 2019) - Bethell, Erin M.; Ernst, Richard E.; Samson, Claire
ABSTRACT: We present a 1:2, 500, 000 geological map of the Alpha Regio (V-32) quadrangle, Venus. The V-32 quadrangle extends from 0° to 25 S, 0°to 30° E with an area of approximately 7, 600, 000 km 2 . Geological mapping was conducted using full resolution (maximum 75 m/pixel) SAR, altimetry and stereo-derived topography data from NASA's Magellan mission in ArcGIS 10.5. Nearly 40, 000 lineaments were mapped. The oldest unit, tessera terrain, is present in two major regions: Alpha Regio and Minu-Anni Tessera. Two major fracture belts, both oriented approximately NNW-SSE, and four minor fracture belts have been identified and characterized. Two previously unrecognized wrinkle ridge trends of radiating and circumferential orientation have also been identified in the northeastern corner of the quadrangle. A total of 77 geological units were mapped. Plains material, previously mapped as global regional plains units, was divided into 27 units. Earlier estimates of the diameters of several coronae have been extended by hundreds of kilometres.